2022
DOI: 10.2196/35310
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Diagnosis and Risk of Death Among Adults With Cancer in Indiana: Retrospective Cohort Study

Abstract: Background Prior studies, generally conducted at single centers with small sample sizes, found that individuals with cancer experience more severe outcomes due to COVID-19, caused by SARS-CoV-2 infection. Although early examinations revealed greater risk of severe outcomes for patients with cancer, the magnitude of the increased risk remains unclear. Furthermore, prior studies were not typically performed using population-level data, especially those in the United States. Given robust prevention me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…In our previous research publications [ 12 , 13 ], we highlighted a significant decline in the incidence of new lung cancer cases during the initial phase. This observation is consistent with widespread global reports documenting similar trends [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Following the decline witnessed initially, we observed a significant resurgence in the incidence of new cases, with an escalation of 79% during the second year of the pandemic.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our previous research publications [ 12 , 13 ], we highlighted a significant decline in the incidence of new lung cancer cases during the initial phase. This observation is consistent with widespread global reports documenting similar trends [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Following the decline witnessed initially, we observed a significant resurgence in the incidence of new cases, with an escalation of 79% during the second year of the pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies have shed light on a concerning phenomenon within the realm of oncology: a marked decline in the detection of new lung cancer cases coupled with a concerning shift in the stage at which these malignancies are being diagnosed. These studies collectively underscore the profound impact that the pandemic, particularly its initial lockdown measures, has had on lung cancer diagnosis and presentation [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the first wave, patients with active cancer were discussed as being a potentially vulnerable group both due to the malignancy itself and immunosuppressive treatments, which has since been verified [ 5 , 6 , 7 , 8 ]. The first cancer studies confirmed that age and comorbidity were risk factors for mortality [ 9 ], and recent studies on large groups have corroborated that advanced age, male sex, and comorbidities are associated with poorer outcomes, especially in patients with active cancer and ongoing treatment [ 10 , 11 ]. A recent study revealed that unvaccinated patients with cancer still constitute a vulnerable group, highly susceptible to SARS-CoV-2 infections with poor outcomes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV-2 infection has a mild course in most people, but in a significant portion of the population, the condition progresses to a severe respiratory disease characterized by hyperinflammatory syndrome, multiple-organ dysfunction, and death [ 8 ]. This is because some patient subgroups, such as the elderly and individuals with chronic conditions, such as hypertension, diabetes, and chronic lung diseases, have been shown to have an increased risk of morbidity and mortality when affected by COVID-19 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature data indicate that patients with cancer undergoing active treatment are at greater risk of developing serious events related to COVID-19, requiring admission to an intensive care unit [ 10 ]. There are reports of early studies from China that demonstrated a 2- to 4-fold increase in COVID-19 mortality among patients with cancer compared to those without cancer, while other smaller studies reported a 29% case fatality rate and worse outcomes among patients with cancer infected with COVID-19 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%